SOME COMMENTS ON THE ACTIVITIES OF OFFICIALS AND INVESTIGATION COMMISSIONS OF THE RUSSIAN EMPIRE ON LAND AND WATER RELATIONS IN TURKESTAN (Scientific journal of the Fergana State University, 2023)
In this article, special emphasis was placed on the activities of officials of the Russian Empire, appointed by the government of the Empire to manage the country of Turkestan in the second half of the 19th - early 20th centuries, and their policy in land and water relations in the region was revealed. Information was also provided on the activities of special working and revision commissions established in Turkestan on isissues of land and water relations, in particular, ownership of land and property, regulation of water resources and the irrigation system in accordance with the interests of the Empire, as well as their results. This article is based on archival documents considered as sources of the period, data from statistical committees, reports of the audit commission and an analysis of research works carried out on this issue in different periods.